Hypersensitivity Pneumonitis: Diagnostic and Therapeutic Challenges - Alberti, Maria Laura; Rincon-Alvarez, Emily; Buendia-Roldan, Ivette; Selman, Moises (Frontiers in Medicine, 2021)
Hypersensitivity pneumonitis (HP) is one of the most common interstitial lung diseases (ILD), that presents unique challenges for a confident diagnosis and limited therapeutic options. The disease is triggered by exposure to a wide variety of inciting antigens in susceptible individuals which results in T-cell hyperactivation and bronchioloalveolar inflammation. However, the genetic risk and the pathogenic mechanisms remain incompletely elucidated. Revised diagnostic criteria have recently been proposed, recommending to classify the disease in fibrotic and non-fibrotic HP which has strong therapeutic and outcome consequences. Confident diagnosis depends on the presence of clinical features of ILD, identification of the antigen(s), typical images on high-resolution computed tomography (HRCT), characteristic histopathological features, and lymphocytosis in the bronchoalveolar lavage. However, identifying the source of antigen is usually challenging, and HRCT and histopathology are often heterogeneous and not typical, supporting the notion that diagnosis should include a multidisciplinary assessment. Antigen removal and treating the inflammatory process is crucial in the progression of the disease since chronic persistent inflammation seems to be one of the mechanisms leading to lung fibrotic remodeling. Fibrotic HP has a few therapeutic options but evidence of efficacy is still scanty. Deciphering the molecular pathobiology of HP will contribute to open new therapeutic avenues and will provide vital insights in the search for novel diagnostic and prognostic biomarkers.